A CURE for a Major Challenge in Phenomics: A Practical Guide to Implementing a Quantitative Specimen-Based Undergraduate Research Experience. Issue 1 (20th February 2020) - Price, S A; Larouche, O; Friedman, S T; Corn, K A; Wainwright, P C; Martinez, C M
Synopsis: The measurement and analysis of phenotypes is often a rate-limiting step for many integrative organismal studies but engaging undergraduate researchers can help overcome this challenge. We present a practical guide to implementing a quantitative specimen-based Course-based Undergraduate Research Experience (CURE), which trains students to collect phenotypic data and mentors them through the entire scientific process using the data they help to collect. Direct access to specimens is not necessary to implement this undergraduate research experience, as recent efforts to digitize museum collections along with online image archives allow data extraction to take place in any classroom. We focus in particular on hypothesis development and quantitative skills, as they are essential for modern biological discovery but are rarely emphasized in traditional lecture-based classes. We have implemented this experience, focusing on collecting and analyzing body shape data across fishes, at two institutions with a total of 39 students. It has so far resulted in 14 talks and 4 posters presented by students at local symposia and 2 scientific papers in preparation with undergraduate co-authors. Moreover, the students had a positive experience that, according to their own assessment, improved their critical thinking and analytical skills as well as their knowledge of science and the scientific process.